Peter Gabriel global citizen - Hegarty, Paul 1967- (Reverb series, 2018)
"Peter Gabriel is one of contemporary music's great experimenters. From his work in the progressive group Genesis, through his pioneering solo albums, to his enthusiastic embrace of world music and new technologies, Gabriel has remained steadfastly consistent in his redefinition of music's boundaries and influence: geographical, virtual and thematic. At the heart of Paul Hegarty's astute analysis is the idea of locatedness: what it means to be in a specific place at a given time, and to reflect on that time and the changes which inevitably occur. Gabriel's work, Hegarty argues, can be understood as a series of reflections on the 'where' of being - and this includes politics, psychology, philosophy, psychogeography and inward reflection. This book offers a nuanced and trenchant insight into this enigmatic musician and his works, an artist whose constant travelling - through identities, influences and media - defines him as one of modern culture's truly global citizens." -- Provided by publisher